1994
DOI: 10.1246/cl.1994.2365
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Total Infrared Intensities of Fluorinated Ethyl Methyl Ethers

Abstract: An excellent linear correlation was found between calculated and experimental total infrared intensities in the region of 500–2000 cm−1 for five partially fluorinated ethyl methyl ethers, HFC-134a, and CFC-11. The calculated results using ab initio molecular orbital method with D95V**(Huzinaga-Dunning’s valence double zeta) show the best linear correlation among basis sets examined in this study. The correlation coefficient with D95V** is 0.9993 although the calculated values are on the average 32% higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
4
2
Order By: Relevance
“…Quoted uncertainties are statistical uncertainties associated with the calibration plot shown in the insert and an additional 4% uncertainty (propagated using standard error propagation techniques) to account for potential systematic uncertainties (see Pinnock et al [1995] for details) and represent the accuracy of the measurements. Our integrated absorption cross section is approximately 13% lower than that of 3.84 × 10 −16 molecule −1 cm reported by Suga et al [1994] and 20% lower than the value of (4.1 ± 0.2) × 10 −16 molecule −1 cm reported recently by Jain et al [2001] (we make the assumption that the integrated cross section reported in the text of Jain et al is base e although the spectrum given in Figure 1 in their paper appears to give absorption cross sections in base 10 units). Within the likely combined experimental uncertainties our result is consistent with that reported by Suga et al [1994].…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Quoted uncertainties are statistical uncertainties associated with the calibration plot shown in the insert and an additional 4% uncertainty (propagated using standard error propagation techniques) to account for potential systematic uncertainties (see Pinnock et al [1995] for details) and represent the accuracy of the measurements. Our integrated absorption cross section is approximately 13% lower than that of 3.84 × 10 −16 molecule −1 cm reported by Suga et al [1994] and 20% lower than the value of (4.1 ± 0.2) × 10 −16 molecule −1 cm reported recently by Jain et al [2001] (we make the assumption that the integrated cross section reported in the text of Jain et al is base e although the spectrum given in Figure 1 in their paper appears to give absorption cross sections in base 10 units). Within the likely combined experimental uncertainties our result is consistent with that reported by Suga et al [1994].…”
Section: Resultscontrasting
confidence: 73%
“…Our integrated absorption cross section is approximately 13% lower than that of 3.84 × 10 −16 molecule −1 cm reported by Suga et al [1994] and 20% lower than the value of (4.1 ± 0.2) × 10 −16 molecule −1 cm reported recently by Jain et al [2001] (we make the assumption that the integrated cross section reported in the text of Jain et al is base e although the spectrum given in Figure 1 in their paper appears to give absorption cross sections in base 10 units). Within the likely combined experimental uncertainties our result is consistent with that reported by Suga et al [1994]. Our result appears to be significantly lower than that of Jain et al In view of this discrepancy we rechecked our calibration but we could not find any errors.…”
Section: Resultscontrasting
confidence: 73%
“…Although the standard deviation (1a) of our measurements of the absorption cross sections was less than 3% (Suga et al, 1994), the measurement error might be larger because of the systematic errors of our instruments. However, it is generally very difficult to estimate the systematic errors in measuring the radiation spectra with a spectrometer.…”
Section: Errorsmentioning
confidence: 81%
“…One of the most fundamental properties for estimating GWP (or HGWP) of a compound is its infrared absorption cross section. In this study, we calculated the cross sections of the compounds based on the transmittance data measured by Suga et al (1994) using an FT-IR spectrometer with a 10 cm-long cell at 296 K and 1.5mmHg. The wavenumber resolution of the measurement is 0.96449cm-1 after apodization.…”
Section: Absorption Cross Sectionmentioning
confidence: 99%
“…As part of ongoing work in our laboratory concerning the environmental impact of industrial replacement compounds, we have measured the infrared absorption cross sections and studied the reactions of OH radicals and Cl atoms with nine HFEs, for which few data are available in the literature: CH 3 CH 2 OCF 3 (R−E 143a), CF 3 CH 2 OCH 3 , CF 3 CH 2 OCHF 2 (HFC-E 245; HFE 245fa2; R−E 245fa1), CF 3 CHFOCHF 2 (Desflurane, Suprane, HFE 236; I 653; R−E 236ea1), CHF 2 CHFOCF 3 , CF 3 CHFOCF 3 (HFE 227), CF 3 CHFCF 2 OCHF 2 , CF 3 CHFCF 2 OCH 2 CH 3 and CF 3 CF 2 CF 2 OCHFCF 3 (Du Pont E 1; Freon E 1). Kinetic data have previously been reported for the OH reactions of CF 3 CHFOCHF 2 , CF 3 CH 2 OCHF 2 , CF 3 CHFOCF 3 , , and CF 3 CH 2 OCH 3 , , whereas rate coefficients are available for the Cl atom reactions of CF 3 CH 2 OCH 3 , CF 3 CH 2 OCHF 2 , , and CF 3 CHFOCF 3 . , Infrared (IR) absorption cross sections have been published for CF 3 CH 2 OCHF 2 , , CF 3 CHFOCF 3 , ,, CF 3 CH 2 OCH 3 , and CF 3 CHFOCHF 2 …”
Section: Introductionmentioning
confidence: 99%